Profil Belajar Siswa dalam Memahami Operasi Hitung Bilangan Bulat Kelas VI Sekolah Dasar - Ghoffar, Moh; Wiryanto, Wiryanto; Rahaju, Endah Budi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
This study aims to analyze and describe the learning profile of six-year-old primary school students in understanding mathematical operations and whole numbers. This research used a qualitative method with a descriptive approach. The research subjects consisted of 30 students of Class VI UPT SD Negeri 5 Gresik who were selected using a purposive sampling method. Data collection was obtained through educational observation, survey research, in-depth interviews, and literature study. Data analysis using the Miles and Huberman method includes data reduction, data presentation and conclusion drawing. The results showed that students' learning profiles can be divided into three groups: (1) 40% of students have a good understanding and can solve the problems correctly, (2) 35% of students have full understanding but still experience problems in mixed tasks, and (3) 25% of students still experience serious problems especially in the efficiency of subtraction and division of negative numbers. From the results of data analysis, it can be concluded that the ability to solve mathematically correct problems of elementary school students in UPT SD negeri 5 Kecamatan still needs improvement,